Evaluation of the Growth and Yield of Hydroponically Grown Bell Pepper at Low Altitudes - Nabila, Athya Kania; Herison, Catur; Fahrurrozi; Suharjo, Usman Kris Joko; Handajaningsih, Merakati; Rustikawati (Akta Agrosia, 2024)
Bell pepper cultivation in low-altitude regions of Indonesia holds significant promise because of increasing domestic and international demand. However, domestic production is not sufficient to meet market needs. This study investigates hydroponic cultivation as a potential solution to low-altitude agriculture. Conducted from November 2023 to January 2024 at the University of Bengkulu Greenhouse เว็บสล็อต | R4shub (10 meters above sea level), the research evaluated the performance of nine bell pepper cultivars using a single-factor completely randomized design (CRD) with three repetitions. The cultivars tested were Red Star F1, Cardinal Star, Hercules, Merah, Yellow Star F1, Golden Star F1, Polaris F1, Orange Bell F1, and Kuning. Results indicated that the Cardinal Star and Polaris F1 cultivars outperformed the others under low-altitude conditions, demonstrating superior growth and yield components. Cardinal Star exhibited the highest fruit weight per plant, whereas Polaris F1 had the highest weight per fruit or fruit size. Key word:  bell pepper, hydroponics, low altitude areas